Kegagalan Gerakan Buruh dan Partai Buruh Pada Pemilu Era Reformasi [The Failure of the Labor Movement And Labor Party in the Reform Era General Election] - Dodi Faedlulloh (Sekretariat Jenderal DPR RI, 2019)
This article explains about the labor movement as an agenda of its organization (labor party) to pursue labor’s aspirations which have been rarely accommodated by government. A possible strategy that can be devised by the labor movement to establish a political party is by developing a strong constituency. This can be achieved by accommodating discussions on important issues from the grassroot level to identify problems and solutions as a form of political education for both labors and the public in general. Moreover, the labor movement needs to promote coordination and avoid inter-organizational disharmony and division. All labor practitioners shall work together and share ideas to shape a committed vision towards establishment of the labor party. Another vital part of this agenda lies in the importance of the implementation of general elections that facilitates the movement of alternative parties. Therefore, current formal administrative rules that hinder the registration of new political parties need to be urgently revised to promote better democracy in Indonesia.AbstrakArtikel ini membahas tentang gerakan buruh dalam agenda membangun partainya sendiri untuk memperjuangkan aspirasi-aspirasi buruh yang selama ini tidak diakomodasi. Strategi yang bisa dilakukan oleh gerakan buruh untuk membuka kemungkinan membentuk partai politik yaitu dengan membangun konstituen yang kuat dengan cara melaksanakan penyerapan aspirasi dari bawah dalam mengidentifikasi masalah beserta tawaran solusi sebagai bentuk dari pendidikan politik bagi rakyat dan buruh. Selain itu, untuk mengurangi fragmentasi antar lintas organisasi, gerakan buruh juga harus segera melakukan konsolidasi. Seluruh aktivis buruh duduk bersama dan bermusyawarah merumuskan tujuan pembangunan partai buruh secara deliberatif. Hal yang tidak kalah penting dalam agenda membangun partai buruh ini yaitu pentingnya penyelenggaraan pemilu yang tidak mempersulit gerak partai-partai alternatif. Oleh karenanya, segala aturan administratif yang memberatkan dalam regulasi pembentukan partai politik saat ini perlu direvisi untuk meningkatkan kualitas demokratisasi dan demokrasi yang lebih baik di Indonesia.